Compton Valance - The Time-travelling Sandwich Bites Back For tablet devices - Brown, Matt (Usborne Publishing Ltd London, 2014)
Compton Valance can time travel using a stinky old sandwich. But now his evil brother has stolen the sandwich and is causing chaos. It's up to Compton and his mate Bryan to stop Bravo before the universe implodes. Yes, really.